PROJECT-BASED LEARNING AS A PEDAGOGICAL PATHWAY TO ENTREPRENEURIAL COMPETENCE IN POSTGRADUATE EDUCATION: EVIDENCE FROM QUALITATIVE INQUIRY - Nur Hidayat Cahyono; Marsini (EDUCATIONE, 2026)
Rapid economic shifts, technological acceleration, and changing labor-market structures require higher education to prepare graduates who are not only academically capable but also creative, innovative, independent, and able to make responsible decisions under uncertainty. This study aimed to examine how project-based learning (PBL) strengthens the entrepreneurial mindset of postgraduate students and to identify the learning processes that facilitate the internalization of entrepreneurial values. A qualitative descriptive design was employed, using direct classroom observation, in-depth semi-structured interviews with postgraduate students and course instructors, and document analysis of course plans and student project reports. Data were analyzed thematically through iterative reduction, display, and conclusion drawing, supported by source and technique triangulation. Findings indicate that PBL positively influenced students’ critical thinking, creativity, collaboration, and problem-solving in authentic entrepreneurship-related tasks. Active engagement across project phases (planning–implementation–evaluation) fostered innovation, accountability, self-confidence, and opportunity recognition, while bridging conceptual understanding with practical entrepreneurial action. The study concludes that PBL is an effective and contextually relevant approach for strengthening postgraduate students’ entrepreneurial mindset and should be integrated more systematically within graduate curricula. Practically, the results inform curriculum design and instructional strategies for entrepreneurship development in higher education. Future research should use longitudinal and mixed-method designs to measure sustained outcomes (e.g., entrepreneurial self-efficacy, intention, or venture creation) across disciplines and institutional contexts.